EVALUATION OF REBOUND TONOMETRY IN RED-EARED SLIDER TURTLES (TRACHEMYS SCRIPTA ELEGANS) - Delgado, Cherlene (2013)
OBJECTIVE: To evaluate feasibility and accuracy of intraocular pressure (IOP) measurement by rebound tonometry in adult red-eared slider turtles and determine the effects of manual and chemical restraint on IOP. ANIMAL STUDIED: Seventeen adult red-eared slider turtles. PROCEDURES: IOP was measured with TonoLab® and TonoVet® tonometers in conscious, unrestrained turtles. To evaluate the effects of manual restraint, turtles were restrained by digital pressure on the rostral head or proximal neck. The effect of two chemical restraint protocols (dexmedetomidine, ketamine, midazolam [DKM] and dexmedetomidine, ketamine [DK] subcutaneously) on IOP was evaluated. Triplicate TonoLab® and TonoVet® readings were compared to direct manometry in 3 ex vivo turtle eyes. RESULTS: TonoLab® correlated better with manometry at IOPs <45 mm Hg than TonoVet® (linear regression slopes of 0.89 and 0.30 respectively). Mean (±SD) IOP in unrestrained conscious turtles was significantly lower (P<0.01) with TonoLab® (10.02 ± 0.66 mmHg) than with TonoVet® (11.32 ± 1.57 mmHg). Manual neck restraint caused a significant increase in IOP (+6.31 ± 5.59 mmHg), while manual rostral head restraint did not. Both chemical restraint protocols significantly reduced IOP (DKM: −1.0 ± 0.76 mmHg,; DK: −1.79 ± 1.17) compared to measurements in conscious unrestrained turtles. CONCLUSIONS: Chemical and manual neck restraint affected IOP. Rostral head restraint had no significant effect on IOP and is, therefore, recommended as the appropriate restraint technique in red-eared-slider turtles. TonoLab® measurements estimated actual IOP more accurately, within physiologic range, than measurements obtained using the TonoVet®.